Roteiro para implementação lean healthcare em hospitais - Grasiani, Alex (2022)
As well goods and services organizations, hospitals need and seek to improve their operational performance in order to provide quality service to the patients and have a profitable and viable business. According to WHO, global health costs are increasing and already consume 10% of global GDP, high costs considering the estimated 5 million deaths per year are their results of low-quality medical care in low-income countries, and average income. In this way, good management that allows the delivery of a high-quality service to patients and that ensures a suitable environment for the people who work there, becomes of great importance. The search for better performance and cost reduction has led hospitals to look for methodologies such as Lean Manufacturing, a philosophy based on continuous improvement and elimination of waste in the entire value stream. In general, managers are unaware of this philosophy, its methodology and tools. In this context, this work developed a guide to assist and guide those responsible for these organizations on how to start the Lean implementation in hospitals, contributing to greater efficiency in the use of resources and improvements in the provision of healthcare services to customers and a better working environment for employees in this sector. First, bibliographic research was carried out to build a theoretical basis for the elaboration of the roadmap. We searching for bibliographies aligned with the theme of the study in scientific databases, using a structured process of formation of ProKnow-c bibliographic portfolio. Afterwards, the roadmap was prepared based on the studies and all the knowledge added by the PB, also being considered evidence from other studies found in the literature. This study has the following contributions: (i) “practice” an applicable and relevant implementation roadmap to assist hospital managers in the development and improvement of their operational practices; and (ii) "academic", the creation of a roadmap to start the implementation of Lean Healthcare based on scientific, comprehensive and structured research, so that it can help researchers regarding the applicability, improvement and evolution of studies on this topic in healthcare organizations.